Retinal vein occlusion and the prevalence of lipoprotein abnormalities. - Dodson, P M (1982)
Ninety-nine patients with retinal vein occlusion (40 with central, 59 with branch vein occlusion) were investigated for the prevalence of associated diseases for comparison with an age-matched control group. There was a significantly increased prevalence of hyperlipidaemia (p less than 0.001) and hypercholesterolaemia (p less than 0.001) in the group with branch retinal vein occlusion and of hyperlipidaemia (p less than 0.001) and hypercholesterolaemia (p less than 0.02) in the group with central retinal vein occlusion compared with controls. An increased prevalence of hypertriglyceridaemia (p less than 0.001) was also found in patients with central vein occlusion. Other associations were noted (hypertension and oestrogen therapy). Increased serum cholesterol concentrations were found in patients with central vein occlusion (p less than 0.05) and branch vein occlusion (p less than 0.001) compared with controls, and similar tendencies were noted for levels of LDL and HDL cholesterol. Patients with central vein occlusion also had raised levels of serum triglyceride (p less than 0.001) and VLDL-triglyceride (p less than 0.05). The occurrence of both central and branch vein occlusions may be associated with an increased prevalence of hyperlipidaemia and hypertension. Increase of serum lipids may contribute to the aetiology of vein occlusion by altering plasma viscosity or affecting platelet function.